CASE MANAGERS’ EXPERIENCES IN HANDLING PERSONAL DATA IN THE CASE MANAGEMENT PROCESS - Virbalienė, Rita; Jusel, Margarita; Čižikienė, Janina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article aims to uncover the personal data protection requirements within the case management process and outline areas for improvement. Objectives include analyzing case management, assessing families in social risk, and discussing personal data protection's concept and necessity in case management. The study examines factors influencing personal data protection in case management and identifies opportunities for improvement when working with families facing social risks. Participants are Vilnius-based case managers with at least one year of social work education and experience. Research methods involve analyzing literature, conducting interviews, and evaluating gathered data. The application of case management to families in social risk is viewed as a complex system, with a coordinated support network reducing social risk factors. Personal data is defined as information identifying an individual, necessitating protection due to technological advancements. The study reveals case managers lack knowledge about personal data protection requirements but strive to adhere to prudent principles. Institutional fear impedes information gathering from various sources due to concerns about violating personal data protection.